Utilization of Water-Soluble Chitosan as Antiseptic Hand Sanitizer - Anies Chamidah; Christina Nur Widiyanti; Nahda Nur Fabiyani (Universitas Gadjah Mada, 2019)
Shrimp wastes produced by manufacturers are mostly limited to be utilized by small industries. They only can turn the waste into chips and shrimp pastes even though it can be used as chitosan. The scarcity of shrimp waste utilized as chitosan is often constrained due to the lack of chitosan dissolve in water caused by the length of the molecular chain. In order to optimize the chitosan utilization, depolymerization is used; such as using H2O2. Chitosan depolymerization enables chitosan to be water soluble and has a high antibacterial ability, which can be applied as an antiseptic of hand sanitizer which has been derived from synthetic materials. The used method is an experimental method which includes the processing of making water-soluble chitosan with test parameters of deacetylation, solubility, moisture content, and yield. Furthermore, the manufacture of hand sanitizers is carried out in vitro and in vivo. The results showed that water-soluble chitosan can be made at 13% H2O2 concentration at 40°C with deacetylation degree 94.21%, 90% solubility, 10.60% moisture content and 3.5% yield. Moreover, after becoming a hand sanitizer, it was able to inhibit Escherichia coli and Staphylococcus epidermidis bacteria at concentrations of 120 mg/ml, respectively 19.53 mm and 21.12 mm, which were relatively strong. Resulted in MIC values 0.28% and 0.27%, and MBC values 1.12% and 1.08%, and also without causing irritation or edema on mouse skin.